Precision Medicine: The Future of Medicine Tailored to Individual Patients - Ermelinda da Costa Monteiro; Joaquim Pinto (Penelitian dan Pengembangan Ilmu, 2024)
Genome sequencing technology and genomic analysis have become important tools in the realm of personalized medicine, revolutionizing diagnostic and treatment strategies tailored to each patient individually. This systematic literature review explores the implications of genome sequencing and analysis technologies in the context of personalized medicine, with the aim of clarifying their potential and challenges. Through a thorough examination of the relevant literature, including studies of genome sequencing technologies, pan-genome analysis, and the integration of genomic data in clinical decision making, this review provides insight into the current state and future directions of personalized medicine. These findings underscore the importance of genomic literacy, cross-disciplinary collaboration, and ethical considerations in realizing the full potential of personalized medicine. By highlighting advances, limitations, and implications of genome sequencing and analysis, this review contributes to the ongoing discourse on precision medicine and informs research and clinical practice in this rapidly developing field.